Securing Web-Based E-Voting System Using Captcha and SQL Injection Filter - Amiruddin Amiruddin; Apriza Noer Ramadhan; David Herdianto (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2020)
The electoral system is very necessary in the democratic life of students, especially to elect a senate chairman in a higher education environment. The use of conventional electoral system is slow, inefficient, and insecure compared to that of electronic-based because it requires a long time for the registration to implementation and counting of votes; use a lot of papers; and it raises the potential for manipulation of ballot papers. In this research, we developed a student electoral system that is safe from non-human participants and electronic-based called e-voting. The system was built with a web platform using PHP and MySQL programming applications. The system development method follows the System Life Cycle (SLC) which consists of the stages of planning, analysis, design, implementation, and testing of the system. This system implements a security mechanism in the form of verification using captcha and SQL injection filter and is implemented in the activities of Komisi Pemilihan Umum Mahasiswa (KPUM). System testing to measure the suitability of implementation with the needs was done using a blackbox method. The result of this research is an e-voting system that satisfies the prevention test of SQL injection and non-human participants attacks